Body Weight Satisfaction, Comments, Nutrition and Injury Risk in 489 Adolescent Elite Athletes - Fridén, Cecilia; Ekenros, Linda; Hirschberg, Angelica Lindén; von Rosen, Philip (International Journal of Sports Medicine, 2023)
Exposure to critical body weight comments in youth athletes could lead to decreased self-esteem, affect body image, and increase the risk of eating disorders and cause depressive symptoms. The aim was to explore differences between sex, body mass index, sports type, with regards to body weight satisfaction, exposure to critical body weight comments from their coach and nutrition status in adolescent elite athletes. A questionnaire about body weight, critical body weight comments and nutrition was distributed to 489 adolescent elite athletes and injury prevalence was monitored across 20 weeks. The results showed that almost one in four athletes (n=116, 24%) was not satisfied with their weight and 12% (n=59) had received critical body weight comments from their coach. Of the athletes who were unsatisfied with their body weight (n=116), 47% wanted to lose weight (n=55). A significant (p<0.05) higher proportion of ice hockey players and swimmers used nutritional supplements, were unsatisfied with their body weight, and were more exposed to critical body weight comments compared to athletes from other sports. Adolescent elite athletes as young as 15–16 years old are exposed to critical body weight comments from their coach and experience challenges with body weight satisfaction that is partly dependent on the sport-specific context.
Keywords: young athlete; body weight; coach; nutrition